2018
DOI: 10.1111/apm.12908
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic phenotype is preserved in myotubes established from type 2 diabetic subjects: a critical appraisal

Abstract: Cultured human myotubes offer a unique model to distinguish between primary and environmental factors in the aetiology of insulin resistance in human skeletal muscle. The objective of this review was to summarize our and other group studies on insulin resistance in human myotubes established from lean, obese and type 2 diabetes (T2D) subjects. Overall, studies of human myotubes established from lean, obese and T2D subjects clearly show that part of the diabetic phenotype observed in vivo is preserved in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 196 publications
(538 reference statements)
1
6
0
Order By: Relevance
“…Importantly, imprinting of muscle satellite cells appears to be relatively stable, and it can persist in vitro across many passages of cells (Covington et al . 2015; Gaster, 2019). Seaborne et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, imprinting of muscle satellite cells appears to be relatively stable, and it can persist in vitro across many passages of cells (Covington et al . 2015; Gaster, 2019). Seaborne et al .…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a very limited number of studies have explored the impact of relatively short term in vivo interventions on the in vitro phenotypes of cultured muscle cells (Sparks et al 2013;Hinkley et al 2017;Lund et al 2017). Importantly, imprinting of muscle satellite cells appears to be relatively stable, and it can persist in vitro across many passages of cells (Covington et al 2015;Gaster, 2019). Seaborne et al (2018a,b) showed that even acute exercise-induced changes in methylation of specific genes related to exercise adaptive response can persist in skeletal muscle for as long as 22 weeks.…”
Section: Metabolic Dysfunction Persists In Cultured Myotubes From Patmentioning
confidence: 99%
“…Interestingly, we and others have previously shown that cultured muscle cells generated from type 2 diabetic subjects have reduced insulin-stimulated glucose uptake and glycogen synthesis compared to cells from non-diabetics (McIntyre et al, 2004, Bakke et al, 2015, Gaster et al, 2002, and thus it is believed that the reduced insulin action results partly from genetic and partly from epigenetic changes (McIntyre et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…To that end, we employed the human SkM cell system (Henry et al, 1995). Multiple investigators have shown that human SkM satellite cells, when cultured and differentiated to myotubes display many of the properties of intact muscle, including T2D-related differences in glucose and fat metabolism (reviewed in Aas et al, 2013;Gaster, 2018), protein expression (Al-Khalili et al, 2014) and, most important to the current goals, secretory profile (Ciaraldi et al, 2016;Massart et al, 2016). Media conditioned by culture with myotubes, was taken as a surrogate for secretion into the extracellular space, and ultimately into the circulation.…”
Section: Discussionmentioning
confidence: 99%